Cryptocurrency dalam Perspektif Etika Investasi Berbasis Agama Islam - Nurika Indah Saffela; Eko Suyono (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Cryptocurrency as a form of financial technology innovation has sparked widespread discourse in Islamic economics, particularly regarding its ethical status and halal status as an investment instrument. This study aims to systematically review the literature discussing cryptocurrency from the perspective of Islamic investment ethics using a conceptual approach based on normative-theoretical analysis. The research employs a literature review method on 16 selected scientific articles from 2020 to 2025, which address issues of Sharia legality, intrinsic value, asset linkage to the real sector, and the principles of maqashid al-shariah. The results of the study indicate that the majority of research assesses cryptocurrency as having characteristics that are prone to violating the principles of riba, Gharar, and maysir, particularly due to high volatility, the absence of underlying assets, and the dominance of speculative activities. However, some contemporary approaches suggest a contextual interpretation based on maqashid al-shariah, especially if cryptocurrency is directed toward productive purposes and the welfare of the community. The blockchain technology underlying cryptocurrency is also seen as having the potential to realize more inclusive and transparent Islamic finance. The study concludes that the ethical status of cryptocurrency is highly dependent on the context of use, technical structure, and normative oversight by Shariah authorities. Therefore, an interdisciplinary evaluative framework combining fiqh muamalah, Islamic finance theory, and digital technology ethics is needed to assess the suitability of cryptocurrency assets more comprehensively.